DAMPAK PERKEBUNAN BESAR KELAPA SAWIT TERHADAP KESEJAHTERAAN RAKYAT - Muhammad Subardin (Jurnal Ekonomi Pembangunan, 2006)
The development of oil palm plantation increase sharply in Kikim of Lahat District. Howefver, the development was not folowed by the improvement of people welfare (ie : villagers income) near by the plantation.This research attemps to answer the impact of oil palm plantation on villagers welfare. The result shows that health, housing and settlement facility, education level, as well as loosing land (because plantation needs alarge amount of land), reflects the lower condition of villagers.The decrease of quality of life people surrounding oil palm plantation relatively become very low Keywords : Poverty, income distribution, welfare